Comprehension and retention of the concepts in mitosis and meiosis in high school biology through an interactive learning object enhanced independent study - Hapin, Hemmie S (University of the Philippines Visayas, 2014)
This study was undertaken to determine the effects of interactive learning objects in enhancing comprehension and retention of second year INHS-SSC student of the concepts in biology about mitosis and meiosis. It also sought to determine the : (a) level of comprehension in mitosis of second year INHS-SSC students taught using interactive learning objects ; (b) level of retention in mitosis of second year INHS-SSC students taught using interactive learning objects ; (c) level of comprehension in meiosis of second year INHS-SSC students taught using interactive learning objects ; (d) level of retention in meiosis of second year INHS-SSC students taught using interactive learning objects ; e) determine the students'perception of the effectiveness of interactive learning objects in mitosis and meiosis. All second year INHS-SSC students SY 2012-2013 had lessons in mitosis and meiosis using interactive learning objects. Validate teacher-made comprehension and retention test were given. mean and standard deviation were used to determine the students' level of comprehension and retention. To establish the difference in the level of comprehension and retention, t-test was used. The students were requested to write an essay about the interactive learning objects using the three guide questions. Thematic Data Analysis was used in analyzing the essay and the Focus Group Discussion. The FGD results revealed that the ease of use and the clarity of presentation were the students' reasons for liking the ILO. All of them agreed that the ILO was suited for the topic and suggested the improvement of including audio, slow motion button and the improved printed guide materials. All students affirmed that the ILO was presented according to their level. It was appropriate to high school students and manipulation of the ailo was also easy for them.Students' suggestions on other ways the ILO can be used are for library, classroom and research.